Virtual university and educational transformation in the context of the pandemic (Revista Innova Educación, 2022)
The abrupt change of the pandemic implied the transformation of traditional education to a virtual one, with numerous shortcomings, both in the organization, methodology, strategies, and instruments used. The article's objective was to deepen the knowledge found on the impact of the virtual university on educational transformation during the Covid-19 pandemic. The methodology used was a literature review. Different searches of reliable and recently published sources were carried out in the Scopus database. The following 4 points were prioritized: global context, ICT, e-learning, the emotional aspect of students and teachers. The results indicate that the adaptation to an online education highlighted the significant gaps in the sector, affecting both students and teachers, who presented a lack of motivation in their academic work. It is concluded that virtual education is in total development. Therefore, institutions must improve their entire organization to adapt to the new form of teaching.
Keywords: Student adaptation; distance education; higher education; information technology; educational technology